Food safety practices of the shellfish oyster (Magallana bilineata) and green mussels (Perma viridis) retailers in the Philippines - Rustia, Abigail S.; Lopez, Crisanto M.; Barrios, Erniel B.; Tanay, Dennis D.; Lagazon, Patricia Mae M.; Palomeno, Antonio M., Jr.; Gosilatar, Juan Carlo G.; Bayangos, Roel Anthony S.; dela Cruz, Denise Anne B.; Dalmacio, Leslie Michelle M. (2025)
Shellfish retailers serve as the critical final link between producers and consumers, playing a vital role in maintaining the safety and quality of oysters and mussels before reaching the consumers. Having baseline information on their food safety practices can then be useful in identifying gaps and strengthening regulatory efforts to ensure public health protection. A study was conducted to evaluate the implementation of appropriate food safety practices by shellfish retailers in key shellfish-producing provinces of the Philippines (Capiz, Cavite, and Pangasinan). A targeted sampling of retailers (n = 111) was employed to assess compliance with the Code of Practice for Fish and Fishery Products and existing Philippine National Standards for good aquaculture practices (GaqP). The study showed that shellfish retailer respondents predominantly adhered to essential food safety practices such as maintaining clean retail stalls, ensuring proper waste disposal, and visually inspecting shellfish for quality. However, significant gaps were identified, including limited use of temperature monitoring during storage and transport, inadequate segregation of shellfish from other seafood being sold, and a lack of proper labeling of retail products. Results also highlighted the reliance on verbal agreements in transactions and the limited capability of retailers to ensure food safety. These findings underscore the critical need for enhanced food safety training, infrastructure support, and regulatory enforcement to bridge existing gaps. The promotion of GAqP in shellfish retailing is vital to safeguard public health and ensure the production and distribution of high-quality, safe shellfish.
Keywords: Food safety; Shellfish; Mussels